THE EVALUATION BLACK SPOT LOCATION AND ACCIDENT RISK OF COT PAYA INTERSECTION ACEH BESAR DISTRICT - Rifki Hidayat; Cut Nawalul Azka; Tamalkhani Syammaun; Muhammad Aula (Universitas Medan Area, 2024)
As the population continues to increase each year, it leads to an increasing demand for transportation, indirectly raising the risk of traffic issues. Simpang Cot Paya, situated on the Laksamana Malayahati road section in the Baitussalam District of Aceh Besar Regency, serves as a secondary arterial road that connects the regency to the city of Banda Aceh and is consistently congested with traffic. According to the Traffic Division of the Banda Aceh City Police from 2018 to 2022, there were 233 reported traffic accidents in this area. This research aims to identify the factors causing these accidents and propose measures to reduce the accident rate at this accident-prone location. Primary data was gathered through field observations and measurements, while secondary data consisted of accident records provided by the Banda Aceh City Police, which were analyzed using the Accident Equivalent Number (AEK) method, Upper Control Limit (BKA), and the Safety Index (SI) method. Additionally, a road safety audit was conducted at the accident-prone location to identify issues that may contribute to traffic accidents and to suggest measures to reduce the risk of accidents. An overall analysis indicates that the highest accident vulnerability occurred in 2018 with the highest AEK value of 126, the highest BKA reaching 2.36, and an SI of 2.36. However, the highest material losses were recorded in 2020, amounting to Rp. 26,600,000. This increase in losses was due to a rise in the number of accidents in 2020, totaling 27, and a higher number of minor injuries, amounting to 29 individuals. In other words, if a location has a Safety Index (SI) greater than 1, it is considered a black spot for accidents. The audit revealed several issues, including fading road markings and a lack of road signs and other road infrastructure. Proposed solutions to address these issues include repainting faded road markings and adding road signs and necessary road infrastructure to improve road functionality.